Effects of obstacle height on obstacle crossing in mild Parkinson's disease - Vitorio, Rodrigo; Pieruccini-Faria, Frederico; Stella, Florindo; Gobbi, Sebastiao; Bucken Gobbi, Lilian Teresa [UNESP] (Elsevier B.V., 2010)
The aim of this study was to compare the locomotor behavior of people with Parkinson's disease (PD) and healthy older adults during obstacle negotiation, both in the approaching and crossing phases. Twelve people with idiopathic PD, with mild to moderate disease, and 12 healthy individuals (CG) walked across an 8 m pathway for three obstacle conditions: no obstacle, low obstacle and high obstacle. Each performed five trials for each obstacle condition. Performance was more disturbed for the high obstacle than the low obstacle. During the approach phase, people with PD demonstrated shorter stride length (F(1,22) = 8.55, P = 0.008) and greater stride duration (F(1,22) = 7.371, P = 0.013) than controls. Those with PD also increased their stance phase durations (F(1,22) = 7.426, P = 0.012) for both obstacle conditions, while the CG maintained comparable step durations for all conditions. For the crossing phase, people with PD demonstrated shorter step length (F(1,22) = 9.699, P = 0.005) over the obstacle. Leading limbs were closer to the obstacle, before and after crossing. Thus PD hypokinesia compromises the approach and crossing phases of obstacle negotiation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Parkinson's disease; Adaptive locomotion; Obstacle avoidance